Is it time to relax nephrogenic systemic fibrosis guidelines and safely offer magnetic resonance imaging to more patients? - Al-Chalabi, Saif; Chrysochou, Constantina; Kalra, Philip A. (Quantitative Imaging in Medicine and Surgery; Vol 9, No 11 (November 15, 2019): Quantitative Imaging in Medicine and Surgery, 2019)
Nephrogenic systemic fibrosis (NSF) is a potentially fatal fibrosing disorder that involves the skin and other internal organs. It is almost always associated with an advanced degree of chronic kidney disease (CKD) or acute kidney injury (AKI). Advances in medical knowledge underpinned some understanding of the pathophysiology and aetiology of this condition which then led to the emergence of strict guidelines for the use of gadolinium (Gd) enhanced MRI scans (Gd-MRI).